Profil Kemampuan Berpikir Kritis Calon Guru Sekolah Dasar dalam Memecahkan Masalah Geometri Berbasis Etnomathematika - Nurita Primasatya; Ilmawati Fahmi Imron; Erwin Putera Permana (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2025)
This study aims to analyze the critical thinking skills of prospective elementary school teachers in solving ethnomathematics-based spatial geometry problems. Critical thinking skills are essential skills for prospective teachers in facing the challenges of modern education. This study uses a descriptive qualitative approach with four final year students of the PGSD Study Program, UN PGRI Kediri as subjects who are classified into two categories, namely high and low ability. Data were collected through problem-solving tests and interviews based on Ennis' critical thinking indicators, which include simple explanations, basic skills, strategies and tactics, conclusions, and further explanations. The results showed that low-ability subjects were only able to achieve three of the five critical thinking indicators, namely providing simple explanations, building basic skills, and drawing conclusions. Meanwhile, high-ability subjects were able to meet all critical thinking indicators. This study confirms that critical thinking skills can be developed through ethnomathematics-based problem presentation, which links mathematical concepts to local culture.